STUDI KOMPARASI PERUBAHAN TIPE KARBURATOR TERHADAP UNJUK KERJA MESIN MOBIL MATARAM PROTO - Rahmadi, Apri (Jurnal Teknik Mesin, 2014)
This research done to determine the effect of changes in the type of carburetor on the engine performance Mataram Proto. Proto Mataram car is energy-efficient three-wheel vehicle made for the purpose of energy-saving vehicles competition. In this study, the two carburetor is used, the first is Keihin carburetor venturi diameter of 16 mm and the second is the carburetor carburetor venturi Honda GX35 with a diameter of 8 mm. This research was conducted in the automotive laboratory, Institute of Science & Technology AKPRIND Yogyakarta.Testing the engine performance and exhaust emissions done twice, first using 16mm Keihin carburetor and the second using a carburetor Honda GX35. Both tests are done at 2000 rpm up to 6000 rpm interval 500 rpm intervals and retrieval of data in the form of power, torque, fuel consumption and exhaust gas emsisi done at the same time on each test.The result is the use of carburetor Honda GX35 lower the average power of 3.47%, 3.43% torque, specific fuel consumption by 14.2%, CO by 28.96%, and 21.02% for HC . However, there was an average increase in the concentration O2and CO2 respectively 35.71% and 0.75%.